A study on “Human resource analytics for decision making in international business machine in India and United States” - Gohain, Angkita Borpatra; Saikia, Archana (The journal of contemporary issues in business and government, 2021)
For any organization, human resources (HR) are important. It brings with it, in addition to experience, the capacity and technical skills that are essential for any organization’s long-term success. Organizations have often had trouble determining the efficiency, status, and opportunities of their human resources. Organizations are looking for even more intelligent choices, from attracting the right talent to maintaining the best talent. HR-analytics has been mostly used in the Western IT industry, but it is now making inroads in the Indian IT market as well. HR analytics has a lot of potential in the Indian IT industry, but HR systems, teams, and people skills have a lot of flaws. This research explores the advantages and disadvantages of HR analytics, as well as the role of HR analytics in decision-making at IBM, a major player in the global IT industry. HR engagement, ethics in analytics, and artificial intelligence in HR and analytics are the main factors in IBM’s better use of HR analytics in better business decisions, according to the study’s findings.